2015
DOI: 10.1159/000441310
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Advanced Pancreatic Cancer and Hyperbilirubinaemia: Review and German Expert Opinion on Treatment with nab-Paclitaxel plus Gemcitabine

Abstract: In patients with advanced unresectable pancreatic cancer, the prognosis is generally poor. Within recent years, new treatment options such as the FOLFIRINOX regimen (5-fluorouracil, leucovorin, irinotecan and oxaliplatin) or the combination of nanoparticle albumin-bound (nab)-paclitaxel plus gemcitabine have shown a clinically relevant survival benefit over the standard gemcitabine in patients with good performance status. Unfortunately, patients with hyperbilirubinaemia, who constitute a substantial proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Alongside genetic variability,4–12 several PDAC epidemiological risk factors have been identified, through cohort studies and case–control studies with varying levels of evidence. Some are considered established: chronic pancreatitis,13 diabetes mellitus,14 obesity,15 glycaemic index,16 adiponectin level,17 lipid levels,18 19 alcohol consumption20 and smoking behaviour,20 while others are suggested: bilirubin level,21 22 vitamin D level23 and Helicobacter pylori infection 24. A small number of protective factors such as allergies,25 intake of statins26 and of aspirin27 have also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside genetic variability,4–12 several PDAC epidemiological risk factors have been identified, through cohort studies and case–control studies with varying levels of evidence. Some are considered established: chronic pancreatitis,13 diabetes mellitus,14 obesity,15 glycaemic index,16 adiponectin level,17 lipid levels,18 19 alcohol consumption20 and smoking behaviour,20 while others are suggested: bilirubin level,21 22 vitamin D level23 and Helicobacter pylori infection 24. A small number of protective factors such as allergies,25 intake of statins26 and of aspirin27 have also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Since nab-P/Gem can pharmacokinetically cause hepatic impairment, care must be taken in patients with hepatic impairment and hyperbilirubinemia, and those patients should be monitored frequently. 23 Results of this study demonstrated that elevated bilirubin and transaminases were not significantly related to OS, suggesting that abnormal laboratory findings caused by malignant biliary obstruction and liver metastasis in patients with MPC are not an absolute contraindication for chemotherapy, but rather an integral part of the inclusion criteria.…”
Section: Discussionmentioning
confidence: 72%
“…Studies using larger cohorts are thus required to determine/confirm the reliability of these miRs as markers to use to differentiate between these two pathologies. In ~70% of cases of pancreatic cancer, the cancer is located within the pancreatic head and the majority of patients develop obstructive cholestasis resulting in increased ALP and GGTP serum levels (23). Significant positive correlations were identified between the expression of miR-210-3p and the activities of the cholestasis-related enzymes ALP and GGTP in patients with PDAC.…”
Section: Discussionmentioning
confidence: 97%